Improving Growth and Production of Cabbage (Brassica oleraceae L.) with Compound Fertilizer Application - Kartika, Juang Gema; Sugiyanta, Sugiyanta; Herdyanti, Tri; Fadilah, Nurul (Journal of Tropical Crop Science, 2017)
Natural soils at times do not supply sufficient amount of nutrients for the crops including cabbage, an important vegetable crop in the tropics. Therefore it is necessary to add fertilizer to supplement the soil nutrients to optimize crop growth and production. A study was conducted to examine seven different rates of inorganic fertilizers Cap Daun at 0.5, 0.75, 1, 1.25 and 1.5 of the recommended rate with the no fertilizer as the control. The results showed that inorganic fertilizer treatment generally improved the growth and yield of cabbage compared to the control. The number of leaf, yield per plant, yield per plot, and yield per ha of cabbage treated with inorganic fertilizers was significantly higher than the control treatment. The recommended rate for cabbage plants is 0.5 recommendation rate, which means applying 136 kg.ha-1 of inorganic fertilizer and urea fertilizer of 64 kg.ha-1 and SP-36 27 kg.ha-1 applied twice, 50% at 1 WAP and the rest at four WAP to get the best results. Keywords: inorganic fertilizer, recommendation rate, relative agronomic effectivity value